Thiol Reactive Probes and Chemosensors - Hanjing Peng; Weixuan Chen; Yunfeng Cheng; Lovemore Hakuna; Robert M. Strongin; Binghe Wang (2012)
Thiols are important molecules in the environment and in biological processes. Cysteine (Cys), homocysteine (Hcy), glutathione (GSH) and hydrogen sulfide (H2S) play critical roles in a variety of physiological and pathological processes. The selective detection of thiols using reaction-based probes and sensors is very important in basic research and in disease diagnosis. This review focuses on the design of fluorescent and colorimetric probes and sensors for thiol detection. Thiol detection methods include probes and labeling agents based on nucleophilic addition and substitution, Michael addition, disulfide bond or Se-N bond cleavage, metal-sulfur interactions and more. Probes for H2S are based on nucleophilic cyclization, reduction and metal sulfide formation. Thiol probe and chemosensor design strategies and mechanism of action are discussed in this review.